Internet access for vehicles using V2I platform - Lee, Chek Kee (2015)
In recent years, there is an increasing of interest in the field of vehicle communication systems. Vehicle-to-Vehicle (V2V) communications are network used to provide nearby vehicles on traffic information which helps to prevent or avoid traffic accidents. The increase of interest in research regarding V2V communication is partly due to the upcoming trend towards Internet of Things (IoT). Internet of Things is a scenario which all objects in the world are assigned with unique identifiers and the ability to transfer data over a network without any interaction. In this project, we investigate the different usage of Cohda Wireless Roadside Units (RSUs) to extend the infrastructure’s hotspot coverage to moving vehicles along a road and the use of Wireless Access for Vehicular Environments (WAVE). Strategies and protocols are designed for the RSU to provide hotspot services and establishing smooth transition of connection between RSU and the on board unit (OBU). Different simulations are carried out using Cohda Wireless Mk4 boxes and implementation of demonstration for this project.